2006
DOI: 10.1073/pnas.0511008103
|View full text |Cite
|
Sign up to set email alerts
|

Structures of wild-type and mutant human spermidine/spermine N 1 -acetyltransferase, a potential therapeutic drug target

Abstract: Spermidine͞spermine N 1 -acetyltransferase (SSAT) is a key enzyme in the control of polyamine levels in human cells, as acetylation of spermidine and spermine triggers export or degradation. Increased intracellular polyamine levels accompany several types of cancers as well as other human diseases, and compounds that affect the expression, activity, or stability of SSAT are being explored as potential therapeutic drugs. We have expressed human SSAT from the cloned cDNA in Escherichia coli and have determined h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 42 publications
3
82
1
Order By: Relevance
“…The protein has a novel arrangement of 8 ␤-strands and two ␣-helices but, very interestingly, has a fold similar to some acetyltransferases including spermidine/spermine N 1 -acetyltransferase (SSAT) (26). Antizyme and SSAT are the two major factors regulating polyamine homeostasis (2,3).…”
Section: Antizyme and Odc Degradationmentioning
confidence: 99%
“…The protein has a novel arrangement of 8 ␤-strands and two ␣-helices but, very interestingly, has a fold similar to some acetyltransferases including spermidine/spermine N 1 -acetyltransferase (SSAT) (26). Antizyme and SSAT are the two major factors regulating polyamine homeostasis (2,3).…”
Section: Antizyme and Odc Degradationmentioning
confidence: 99%
“…SSAT1 Activity Is Required for Suppression of GFP or GFPeIF5A Expression-To determine whether the acetylation activity of SSAT1 is required for suppression of the reporter protein expression, we first compared the effects of the two SSAT1 mutants R101A and R101K with the wild type enzyme. From the crystal structure (24) and earlier mutagenesis study (30,31), Arg 101 is known to be important for the binding of acetyl-CoA. Substitution of this residue with Ala (or Lys) caused loss of activity to less than 5% of the wild type enzyme.…”
Section: Tablementioning
confidence: 99%
“…2, A and B), indicating that the acetylation activity of SSAT1 is crucial for the SSAT1 effects. We further tested additional mutant enzymes, with mutation at the catalytic site (Y140A and Y140F) (24), and those with high K m values for spermidine (30), E152K, R155A, H26A, L56F (32), L56A, and E152K/R155A. None of these SSAT1 mutant enzymes effectively blocked the expression of GFP (data not shown), indicating that the SSAT1 activity is required for the effect.…”
Section: Tablementioning
confidence: 99%
“…Bottom: the molecular surface of SSAT (left) and TLAT (right) is shown, colored according to element (nitrogen, blue; oxygen, red; carbon, gray; sulfur, yellow), demonstrating the differences between these proteins in surface properties. tion, was the observation that SSAT can self-acetylate at Lys 26 (15). Analysis of the recombinant human protein produced at high concentrations in E. coli showed that half of the monomers had an N-acetyl group on this residue.…”
mentioning
confidence: 99%